Kosztolányi „névszemlélete” és névválasztással kapcsolatos eljárásai az újabb kutatások tükrében - Páji, Gréta (Studia Litteraria, 2018)
Based on the above claims it can be concluded that the research of Kosztolányi’s literary onomastics and “naming practices” is justified by the fact that he is often regarded as one of the “name-sensitive” authors. This paper demonstrates that an interdisciplinary approach to this question, which combines both linguistic and literary aspects, proves to be highly effective in creating a detailed overview of the topic. The study sheds light on the “naming practices” which can be deducted from dezső Kosztolányi’s statements and writings related to naming and on how these approaches are reflected in his prose and harmonise with his views of language. The study provides illustrative examples from the most important and relevant name-related texts and at the same time gives a brief explanation of the author’s naming procedures and strategies, which i analysed in detail in a previous study. As we have seen, both the published and announced volumes of the lifework’s critical edition are of crucial importance for future research in the author’s literary onomastics. These volumes make it possible to compare and visualise the eventual and not-so-rare name changes and the path to finding the right name during the creation of the text.